(untitled) (Research, Society and Development, 2021)
This work aims to present and discuss new possibilities of space / time for teacher training given a world scenario marked by the pandemic of COVID-19. We present and analyze the development of an extension project created by the Student Representation and other collaborators of the Graduate Program in Science Education: Life Chemistry and Health at the Federal University of Santa Maria. The project promoted Online Training Cycles for teachers through the YouTube platform through which 44 lives about different topics related to education. The YouTube channel reached 3,804 subscribers and the lives happened with the participation of 58 speakers from all Brazilian regions. The development of the project during the experienced moment of physical distance applied dialogues and theoretical and practical reflections. reflections between educators on distinct aspects, contributing to processes of reflection and teacher training. In addition, the use of digital technologies enabled greater accessibility and practicality by participants from different locations, overcoming the need for presence.